Aerosol in the GATE area and its radiative properties - Kondratyev, K. Ya, author; Department of Atmospheric Science, Colorado State University, publisher (Colorado State University. Libraries, 1976)
This report summarizes preliminary results of a research program conducted by Main Geophysical Observatory scientists during the GATE (GARP Atlantic Tropical Experiment). The origin and characteristic features of the dust layer are discussed. Inferences of microphysical and optical characteristics of the dust aerosol made from ship data are presented. Chemical analyses of aerosols showed a rather high content of metals. The iron concentration nearly always exceeded 10-5 kg m-3 for aircraft aerosol observations. Extensive data are presented giving spectral and total shortwave radiative flux divergence values for cloudfree, dust and stratoform cloud cases. These data are interpreted in the context of the meteorological conditions and the optical parameters of the aerosol or cloud layer.
Issued simultaneously in the Transactions of the Glavna?i?a geofizicheska?i?a observatori?i?a.
Keywords: Dust; Radiative transfer